Architecture of the Sema3A/PlexinA4/Neuropilin tripartite complex - Defen Lu (Nature Portfolio, 2021)
Secreted class 3 semaphorins (Sema3s) form tripartite complexes with a plexin receptor and neuropilin co-receptor to transduce signals for neuronal axon guidance and other processes. Here, the authors present the cryo-EM structure of the extracellular Sema3A/PlexinA4/Neuropilin1 complex that provides further insights into the interactions among semaphorin, plexin and neuropilin and reveals long flexible linkers in semaphorin and neuropilin that are important for complex formation.